2003
DOI: 10.1590/s0103-97332003000300010
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with competitive reactions: static and dynamical critical behavior

Abstract: We studied in this work a competitive reaction model between monomers on a catalyst. The catalyst is represented by hypercubic lattices in d = 1, 2 and 3 dimensions. The model is described by the following reactions: A + A → A2 and A + B → AB, where A and B are two monomers that arrive at the surface with probabilities y A and y B , respectively. The model is studied in the adsorption controlled limit where the reaction rate is infinitely larger than the adsorption rate. We employ site and pair mean-field appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This result is independent of a and is exactly the same we have obtained in our previous work [4]. This is not a surprise since in the site approximation the probability of a reaction to occur does not depend on the presence of other particles.…”
Section: Site Approximationsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is independent of a and is exactly the same we have obtained in our previous work [4]. This is not a surprise since in the site approximation the probability of a reaction to occur does not depend on the presence of other particles.…”
Section: Site Approximationsupporting
confidence: 90%
“…We found that the ratio b/m ? is (a) 0.251 ( (2) and (c) 0.264 (4). Based on these results we can conclude that…”
Section: Monte Carlo Simulationsmentioning
confidence: 52%
See 1 more Smart Citation
“…From Table II it is clear that the exponents we have obtained follow the relation given by equation (18). We have also considered an arbitrary initial configuration that is different from the natural configuration of the system.…”
Section: Spreading Dynamicsmentioning
confidence: 67%
“…In particular, we are interested in the study of catalytic reaction models with competitive reactions between two types of monomers: the autocatalytic reaction A + A → A 2 [15] and the simple monomer-monomer reaction A + B → AB [16]. This competitive reaction model was studied, at zero temperature, through the dynamical mean-field approximation and Monte Carlo simulations [17,18]. The results showed that the critical exponents of the model are in the DP universality class, and that the absorbing state is unique, with the lattice completely poisoned by monomers of type B.…”
Section: Introductionmentioning
confidence: 99%